Rhizosphere-associated bacterial and fungal communities of two maize hybrids under increased nitrogen fertilization - Liu, Qing; Dai, HongCui; Cheng, Hao; Shao, Guodong; Wang, Liang; Zhang, Hui; Gao, Yingbo; Liu, Kaichang; Xie, Xiaomei; Gong, Junhua; Qian, Xin; Li, Zongxin (Frontiers in Plant Science, 2025)
IntroductionThe selection and application of nitrogen-efficient maize hybrids have significantly bolstered contemporary food security. Nevertheless, the effects of heightened nitrogen fertilizer demand of these crops on the composition and assembly of soil microbial communities in agricultural production require further elucidation.MethodsIn this study, the effects of four nitrogen fertilizer managements on rhizosphere bacterial and fungal community assembly, co-occurrence network and function of two maize hybrids (LD981 and DH605) were compared.Results and discussionFindings revealed that the bacterial community was primarily shaped by deterministic processes, while stochastic processes played a pivotal role in fungal community assembly. N-efficient hybrid DH605 had a more stable microbial network than N-inefficient hybrid LD981. At N3 (130 g N/m2) rate, the bacterial and fungal community networks were the most complex but unstable, followed by N2 (87 g N/m2), N0 (0 g N/m2), and N1 (43 g N/m2) rates. Excessive nitrogen rate (N3) increased the relative abundance of denitrification genes nirK and norB by enriching nitrogen-related genus such as Nitrolancea and Nitrosospira. It led to an increase in the relative abundance of pathways such as cysteine and methionine metabolism and pyruvate metabolism. The effects of management practices (i.e. maize hybrids and N rates) on microbial communities were ultimately directly or indirectly reflected in microbial functions. Our findings illustrate the relationship between the appropriate selection of crop hybrids and management measures in optimizing rhizosphere microbial community assembly and promoting nitrogen use, which is necessary for sustainable food security.